2018
DOI: 10.1097/mat.0000000000000546
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pediatric Ventricular Assist Device Therapy: A Case Report of 2100+ Days of Support

Abstract: Ventricular assist devices (VADs) have been placed as destination therapy in adults for more than 20 years, but have only recently been considered an option in a subset of pediatric patients. A 2016 report from the Pediatric Interagency Registry for Mechanical Circulatory Support revealed only eight pediatric patients implanted with a VAD as destination therapy. Herein, we report the case of an adolescent male with Becker muscular dystrophy who underwent VAD placement in 2011 as bridge to candidacy. He subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the long‐term follow‐up phase, the comprehensive multidisciplinary care team used in the preimplant and immediate postimplant phases must be continued. Recently, Purkey et al 28 published a case report describing their success in a patient with BMD supported for over 5 years on LVAD support, demonstrating that long‐term success is possible in this unique patient population. In addition, a recent study found similar long‐term outcomes after LVAD implantation for patients with muscular dystrophy compared to those with dilated cardiomyopathy from other etiologies.…”
Section: Advanced Hf Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the long‐term follow‐up phase, the comprehensive multidisciplinary care team used in the preimplant and immediate postimplant phases must be continued. Recently, Purkey et al 28 published a case report describing their success in a patient with BMD supported for over 5 years on LVAD support, demonstrating that long‐term success is possible in this unique patient population. In addition, a recent study found similar long‐term outcomes after LVAD implantation for patients with muscular dystrophy compared to those with dilated cardiomyopathy from other etiologies.…”
Section: Advanced Hf Therapiesmentioning
confidence: 99%
“…Furthermore, patients with muscular dystrophy demonstrated stable or improved skeletal muscle function following LVAD implantation 42 . Comprehensive clinic follow‐up also must include the added complexity of equipment review and replacement, as well as ongoing re‐education of patients and caregivers, all of which have been successfully undertaken in both large and small pediatric LVAD programs 28,43 …”
Section: Advanced Hf Therapiesmentioning
confidence: 99%
“…4,5 Destination therapy is a relatively new indication for VAD implanta tion in a small but increasing cohort of children. 6,7 Two review articles describe the principles of hemo dynamic management in VAD patients: optimizing preload, maintaining right ventricular function, and managing sys temic vascular resistance. 8,9 However, there is little litera ture describing clinical experience for VAD implantation from the anesthesia perspective.…”
Section: Introductionmentioning
confidence: 99%